Exploration of an Actin Promoter-Based Transient Expression Vector to Trace the Cellular Localization of Nucleorhabdovirus Proteins in Leafhopper Cultured Cells - Zhang, Xiao-Feng; Xie, Yunjie; Wang, Haitao; Wang, Juan; Chen, Hongyan; Zeng, Tianbao; Zhao, Yibing; Wei, Taiyun (Frontiers in Microbiology, 2018)
Abstract: Continuously cultured cell lines derived from planthopper and leafhopper have greatly facilitated the investigation of rice viruses transmitted by these insects. However, the lack of a suitable transient expression vector has limited their utility. Here, by cloning and analyzing the promoter sequence of the gene encoding cytoplasmic actin from the leafhopper Nephotettix cincticeps, we successfully developed the first efficient transient expression vector for cultured leafhopper cells, which can also be used to express exogenous proteins in other insect culture cell lines, including those derived from Recilia dorsalis leafhopper and Spodoptera frugiperda (Sf9). Furthermore, insertion of the Hr5 viral enhancer element and knockdown of the endogenous Dicer2 gene notably improved the vector’s expression efficiency in leafhopper cells. Using the optimized vector, we have for the first time traced the cellular localization of the proteins encoded by rice yellow stunt virus (RYSV) in cells of its insect vector and demonstrated that P6 protein is a component of the viroplasm.